2012
DOI: 10.1536/ihj.53.263
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Infarct Tissue Characteristics and Left Ventricular Remodeling in Patients With Versus Without Early Revascularization for Acute Myocardial Infarction as Assessed With Contrast-Enhanced Cardiovascular Magnetic Resonance Imaging

Abstract: SummaryLeft ventricular (LV) remodeling following myocardial infarction (MI) is the result of complex interactions between various factors, including presence or absence of early revascularization. The impact of early revascularization on the relationship between infarct tissue characteristics and LV remodeling is incompletely known. Therefore, we investigated in patients with versus without successful early revascularization for acute MI potential relations between infarct tissue characteristics and LV remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…[9][10][11][12] However, due to limitations in spatial resolution, the imaging of the thinner atrial wall is more challenging. Recent advancements in MRI techniques have provided higher-resolution images that enable the localization and quantification of atrial SRM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] However, due to limitations in spatial resolution, the imaging of the thinner atrial wall is more challenging. Recent advancements in MRI techniques have provided higher-resolution images that enable the localization and quantification of atrial SRM.…”
Section: Discussionmentioning
confidence: 99%
“…8,9) The utility of LGE-MRI to characterize ventricular myocardial injury has been confirmed using comprehensive pathological validation studies, and the method is now widely used in clinical practice. [9][10][11][12] Several recent pilot studies that involved electrical and/or pathological validation have reported that cardiac MRI is useful for characterizing transcatheter ablation-induced atrial scar tissue in animal models. 8,13) However, no fundamental pathological validation study has been conducted on the use of cardiac LGE-MRI for the assessment of pre-ablation LA-SRM in AF patients.…”
mentioning
confidence: 99%
“…Wall motion was assigned the following scores: normal wall motion was 0, mild hypokinesia 1, severe hypokinesia 2, akinesia 3, and dyskinesia 4. The wall motion score index was calculated by dividing the sum of scores in each segment by the total number of observed segments [9].…”
Section: Study Populationmentioning
confidence: 99%
“…In addition, chronic medical therapy has been shown to reduce the extent of LV remodeling during follow-up [4][5][6]. Both LV remodeling and infarct tissue characteristics can be assessed with cardiovascular magnetic resonance (CMR) imaging in combination with the contrast enhancement (CE) technique [7][8][9][10]. There is no such thing as a "single cause" of LV remodeling, which can even be observed following successful revascularization procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical examples for this role are the assessment of ischemic cardiac disease, non-ischemic cardiomyopathy, myocarditis, and infiltrative heart diseases. [3][4][5][6][7] However, the myocardial involvement in these different pathologies is sometimes diffuse and can, on the other hand, have myocardial fibrosis as its final product. Both myocardial fibrosis and diffuse myocardial disease pose some challenges to conventional CMR sequences where fibrosis is exclusively detected by late gadolinium enhancement (LGE) MRI that again may miss a diffuse or early disease and is contraindicated in renal dysfunction.…”
mentioning
confidence: 99%